Analisis faktor-faktor yang mempengaruhi pertumbuhan ekonomi di Kabupaten Sarolangun - Rosminah, Rosminah; Nurjanah, Rahma; Umiyati, Etik (e-Journal Perdagangan Industri dan Moneter, 2019)
Investment (PMDN) and government expenditures have on economic growth in Sarolangun Regency. The type of data used is secondary data in the form of time series data for 2000-2017, in the form of data on economic growth, the number of workers, PMDN, and government spending. The analytical method used in this study is multiple linear regression or Ordinary Least Square (OLS). Based on the analysis results indicate that the workforce has a positive and significant effect on economic growth. PMDN has a positive and significant effect on economic growth. Likewise, government spending has a positive and significant effect on economic growth. Keywords: Economic growth, Labor, Domestic investment (PMDN), Goverment expenditure.